2015
DOI: 10.1186/1475-2875-14-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting delay in seeking treatment among malaria patients along Thailand-Myanmar border in Tak Province, Thailand

Abstract: BackgroundMalaria is a major health problem in Thailand, especially in areas adjacent to the borders of Myanmar. Delay in seeking treatment is an important factor in the development of severe complications, death and the transmission of the disease. This study aimed to investigate factors affecting delays in seeking treatment of malaria patients.MethodsA cross-sectional analytic study was conducted in 456 malaria patients along the Thailand-Myanmar border. Patients were selected by stratified sampling from 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 21 publications
2
53
1
Order By: Relevance
“…Tak Province, located at the Thailand-Myanmar border, is usually responsible for the highest number of annual malaria cases (Parker et al 2015, Sonkong et al 2015. Ubon Ratchathani Province, in northeastern Thailand, has never been in the top 10 provinces for malaria incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Tak Province, located at the Thailand-Myanmar border, is usually responsible for the highest number of annual malaria cases (Parker et al 2015, Sonkong et al 2015. Ubon Ratchathani Province, in northeastern Thailand, has never been in the top 10 provinces for malaria incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Evidences showed that most malaria-related deaths in malariaaffected countries occur at home without receiving appropriate medical care, and when care is sought, it was often delayed [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The poor economic conditions, households with a low income as well as no health insurance are an obstacle and limitation to accessing healthcare delivery, causing treatment delays. 11,19,20,26,28 The holistic professional approach to the health of migrant people into mainstream healthcare practices, health policy, and local political policy should lead to promoting equity and quality of healthcare service.…”
Section: Discussionmentioning
confidence: 99%